Two new species of Coccomorpha (Hemiptera: Sternorrhyncha) collected from Japanese silver grass, Miscanthus sinensis (Poaceae) in Okinawa Island, Japan - Tanaka, Hirotaka; Kamitani, Satoshi (Zootaxa, 2021)
Two new species of Coccomorpha collected from Japanese silver grass, Miscanthus sinensis Andersson (Poaceae), in Okinawa Island, Japan, are described based on the morphology of adult females: Aspidiella kijimuna sp. nov. (Diaspididae) and Dysmicoccus bunagaya sp. nov. (Pseudococcidae). Aspidiella kijimuna is similar to A. phragmitis (Takahashi, 1931) but differs from it by having relatively well-developed and recognisable third lobes, and median lobes with rounded apices. Dysmicoccus bunagaya is similar to Trionymus okiensis Tanaka, 2018 but differs from it by having more than eight pairs of cerarii. Keys to all the Japanese species of Aspidiella and Dysmicoccus are provided.